Rare Animal Education Usingaugmented Reality - Hening Artdias; Ridwan Sanjaya; Alb. Dwi Yoga Widiantoro (SISFORMA, 2017)
Indonesia has a lot of the diversity on flora and fauna that can be assets and icon on this area. Unfortunately flora flora and fauna that exist in Indonesia is less reasing. The animals endangered in Indonesia are Javan Rhino , Sumatran Rhino, Sumatran Tiger, Sumatran Orangutan, Sumatran Elephant, Borneo Elephant, Bornean Orangutan and Turtle.They are extinction because destruction of forest habitats, a conflict between humans and animals, trade, hunting, the arrests beyond capacity. [1]. Is that the issue of the extinction of the animals is dominated by human behavior and nature of the wrath of them. For that, education game “Rare Animal” become formulations to raise awareness of endangered species.